Prediction of Average Rainfall for the City of Recife between 2014 and 2023: An Application of the Thiessen Method - Cabral Júnior, José Alves; Soares, Willames de Albuquerque; Holanda, Marco Aurelio Calixto Ribeiro de; Goldfarb, Maurício Costa (Technical and Scientific Journal Green Cities, 2025)
Due to recent climate change, the study and understanding of local climate and the hydrological cycle have become increasingly important, since these changes have led to extreme precipitation events, causing flooding and damage to society as a whole. Recife-PE is one of the cities that suffer from these events. The objective of this study was to estimate the average rainfall in different points of the city of Recife-PE, enabling better planning of local public policies, based on the periods of greatest rainfall and greatest droughts. Rainfall data, from January 2013 to December 2023, were obtained from the National Center for Monitoring and Alerts for Natural Disasters (CEMADEN). Average rainfall was determined by the Thiessen polygon methodology. Data normality was verified by the Shapiro-Wilk test, with a significance of 5% and data trend by linear regression. It was found that the months with the lowest and highest rainfall volumes were October 2016 and May 2022, respectively. The average rainfall values ​​follow a normal distribution and show a slight upward trend. The number of available stations has increased satisfactorily, however, their spatial distribution is inadequate. In order for rainfall determination to be a strong indicator in political decision-making, it is necessary to have a better distribution of rain gauges, in addition to the continued monitoring of average rainfall.
Keywords: Shapiro-Wilk; Climate change; Dispersion